Engines roar at UMPSA as over 120 luxury and antique vehicles roll in - Wallid Wahidi, Hamzah (UMPSA, 2025)
GAMBANG, 27 July 2025 – The usually quiet Chancellery Grounds at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) roared to life today as more than 100 gleaming luxury and vintage cars, along with 20 high-powered motorcycles, arrived in style for the Friendly Reception and Luxury & Antique Car Gathering (Majlis Ramah Mesra dan Perhimpunan Kereta Mewah dan Antik), held in conjunction with the Kuantan Festival 188.